Full predicted energy from nutrition and the effect on mortality and infectious complications in critically ill adults: a protocol for a systematic review and meta-analysis of parallel randomised controlled trials. Issue 1 (December 2015) - Ridley, Emma; Davies, Andrew; Hodgson, Carol; Deane, Adam; Bailey, Michael; Cooper, D.
Abstract Background Whilst nutrition is vital to survival in health, the precise role of nutrition during critical illness is controversial. More specifically, the exact amount of energy that is required during critical illness to optimally influence clinical outcomes remains unknown. The aim of this systematic literature review and meta-analysis is to evaluate the clinical effects of optimising nutrition to critically ill adult patients, such that the entire predicted amount of energy that the patient requires is delivered, on mortality and other important outcomes. Methods A systematic literature review and meta-analysis will be conducted by searching for studies indexed in Medical Literature Analysis and Retrieval System Online (MEDLINE), Excerpta Medica Database (EMBASE), Cumulative Index to Nursing and Allied Health Literature (CINAHL) and the Cochrane Library. Searches will be restricted to English. Studies will be considered for inclusion if they are a parallel randomised controlled trial investigating a nutrition intervention in an adult critical care population, where one arm delivers 'full predicted energy from nutrition' (defined as provision of ≥80 % of the predicted energy required) and the other arm delivers energy less than 80 % of the predicted requirement. Two authors will independently perform title screening, full-text screening, data extraction and quality assessment for this review. The quality of individual studies will be assessed using the 'Risk of Bias' tool, and to assess the overall body of evidence, a 'Summary of Findings' table and the Grades of Recommendation, Assessment, Development and Evaluation system will be used, all recommended by the Cochrane Library. Pending the study heterogeneity that is determined, a fixed-effect meta-analysis with pre-defined subgroup analyses will be performed. Discussion Currently, it is controversial whether optimal energy delivery is beneficial for outcomes in critically ill patients. This systematic review and meta-analysis will evaluate whether delivering optimal energy to critically ill adult patients improves outcomes when compared to delivery of lesser amounts. Systematic review registration PROSPEROCRD42015027512